Trends in honey purchase and consumption in Trás-os-Montes region, Portugal - Ribeiro, Maria (2019)
Honey is considered the only food of animal origin that can be consumed without being processed. The literature presents several reasons why people consume honey, namely, it being a natural and healthy prod- uct known for its dietary, nutritional and medicinal characteristics. Moreover, other reasons for honey’s pur- chase include the product quality; the region of origin; the information available on the product’s label, the brand’s reputation; and the variety, texture, taste, aroma, appearance, packaging and price of honey. Thus, we intend to identify determinant factors on which consumers base their purchasing decision. Therefore, we developed a cross-sectional study based on a non-probabilistic sample of 474 individuals, 399 of whom were honey consumers. We collected the data in the period from March to May 2016 using a questionnaire [1], which we applied directly to consumers in the city of Bragança. Later, we analysed the data with SPSS 23.0 software. The data analysis included a univariate descriptive analysis and a multivariate analysis that in- volved assessment of a binary logistic regression in order to identify the determinant factors for purchasing and consuming honey. The statistically significant parameters included taste, colour, origin, and certifica- tion label, at a significance level of 1 %. These characteristics explained 68.9 % of the consumer’s decision to purchase honey. It is noteworthy that non-consumers considered the certification label important (when purchasing the product to offer to someone), while in the process of decision-making honey consumers val- ued taste, colour and country of origin.